2019
DOI: 10.1124/pr.116.013003
|View full text |Cite
|
Sign up to set email alerts
|

Patient and Disease–Specific Induced Pluripotent Stem Cells for Discovery of Personalized Cardiovascular Drugs and Therapeutics

Abstract: Human induced pluripotent stem cells (iPSCs) have emerged as an effective platform for regenerative therapy, disease modeling, and drug discovery. iPSCs allow for the production of limitless supply of patient-specific somatic cells that enable advancement in cardiovascular precision medicine. Over the past decade, researchers have developed protocols to differentiate iPSCs to multiple cardiovascular lineages, as well as to enhance the maturity and functionality of these cells. Despite significant advances, dru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
118
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 155 publications
(120 citation statements)
references
References 243 publications
(286 reference statements)
2
118
0
Order By: Relevance
“…One limitation of this study is our reliance on hPSC-CMs, which are well-known for their functional immaturity 33 . Moreover, while the in vitro systems we used have been successfully leveraged to model electrophysiological and contractile alterations due to drugs or inherited mutations 34,35 , their application to modeling COVID-19 will require further validation. A recent report by Dolhnikoff et al identified coronaviral particles in the cytoplasm of cardiomyocytes, endothelial cells, and fibroblasts by electron microscopy in the heart of an 11 year-old child who died from multi-system inflammatory syndrome in children (MIS-C) following COVID-19 infection 20 .…”
Section: Main Textmentioning
confidence: 99%
“…One limitation of this study is our reliance on hPSC-CMs, which are well-known for their functional immaturity 33 . Moreover, while the in vitro systems we used have been successfully leveraged to model electrophysiological and contractile alterations due to drugs or inherited mutations 34,35 , their application to modeling COVID-19 will require further validation. A recent report by Dolhnikoff et al identified coronaviral particles in the cytoplasm of cardiomyocytes, endothelial cells, and fibroblasts by electron microscopy in the heart of an 11 year-old child who died from multi-system inflammatory syndrome in children (MIS-C) following COVID-19 infection 20 .…”
Section: Main Textmentioning
confidence: 99%
“…The treatment of CMs with the channel modulator lumacaftor led to a recovery of the pathological phenotype in CMs with Class 2 mutations but not in those affected by Class 1 mutations, showing the importance of genetic background in the pharmacological response [ 98 ]. Even if the use of patient-specific iPSC-based platforms in drug discovery and personalized medicine is advantageous for many aspects, they are not yet completely affirmed in the pharmaceutical industry due to the time-consuming nature and high cost of iPSC production and differentiation processes [ 99 ]. To overcome this issue, Solomon and colleagues have proposed the establishment of a biobank containing several iPSC lines reprogrammed from healthy donors carrying different combinations of human leukocyte antigen (HLA) alleles in order to provide a shared and economic starting point from which iPSC-derived differentiated cells are made available to HLA-matching individuals for drug investigations and precision medicine [ 100 ].…”
Section: Drug Discovery and Personalized Medicinementioning
confidence: 99%
“…To determine whether Col15a1 also stimulates cardiomyocyte proliferation in human cells, we utilized a human iPSC model of LVNC. Our group has previously shown that iPSC-CMs from LVNC patients exhibit defective proliferative capacity in culture 6,19 . We thus investigated whether Col15a1 could rescue this phenotype.…”
Section: Col15a1 Is Expressed In Coronary Ecs and Stimulates Cardiomymentioning
confidence: 99%